64.4k views
0 votes
What is the sum of the rational expressions below? 3x/x+9 + x/x-4

2 Answers

6 votes

Answer:


(4x^2-3x)/((x+9)(x-4))

Explanation:

The sum of two rational expressions is done in the following way:


(a)/(b)+(c)/(d) = (a*d + c*b)/(b*d)

In this case we have the following rational expressions


(3x)/(x+9) + (x)/(x-4)

So:


a=3x\\d=(x+9)\\c=x\\d=(x-4)

Therefore


(3x)/(x+9) + (x)/(x-4)=(3x(x-4)+x(x+9))/((x+9)(x-4))

simplifying we obtain:


(3x(x-4)+x(x+9))/((x+9)(x-4))=(3x^2-12x+x^2+9x)/((x+9)(x-4))\\\\(3x^2-12x+x^2+9x)/((x+9)(x-4))=(4x^2-3x)/((x+9)(x-4))

User Jeckep
by
5.5k points
1 vote

Answer:


(4x^2-3x)/((x+9)(x-4))

Explanation:

We are given the following expression and we are to find the sum of this rational expression below:


\frac { 3 x } { x + 9 } + \frac { x } { x - 4 }

Taking LCM of it to get:


(3x)/(x+9) =(3x(x-4))/((x+9)(x-4))


(x)/(x-4) =(x(x+9))/((x-4)(x+9))


(3x(x-4))/((x+9)(x-4))+(x(x+9))/((x-4)(x+9))


(3x(x-4)+x(x-9))/((x+9)(x-4))


(4x^2-3x)/((x+9)(x-4))

User Meziantou
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.